CAUSES OF DELINQUENCY AMONG STUDENTS AND PEDAGOGICAL WAYS TO ELIMINATE IT - Olimovich, Pardayev Khurshid (Journal of Higher Education and Academic Advancement, 2024)
This article discusses the causes of delinquency among students and pedagogical ways to eliminate it, as well as the violation of personal behavior. According to the author, in order to turn the behavior of students with a tendency to commit crimes in a positive direction, it is necessary to instill in them high qualities such as responsibility, pride, responsibility, trust. For this, it is important to give them tasks taking into account their age, strength, abilities and interests. As a result of entrusting them with the task of managing a small team, a sports section, a "living corner", negative behaviors can be reduced